Chief Factors in the Reconstruction of Teacher Identity: Analysis of Results of a Questionnaire Survey Conducted at Five Private Middle or High Schools in the Greater Tokyo Area, Japan - Furuichi, Yoshifumi (ATIKAN, 2014)
ABSTRACT: This research is on career formation for teaching personnel at private schools. A questionnaire survey of full-time teachers at five middle schools or high schools was conducted in the Greater Tokyo Area, Japan. Different results based on age (difference between teachers 40 and above, and those under 40) were obtained as a result of this analysis. In the case of teachers under 40, the school where they worked, the quality level of their students, and efforts made by the school did not have a significant effect on their teacher professional identity. The teacher professional identities of those 40 and above, however, were significantly influenced by such factors as student quality levels, school management policies, including positive efforts to activate schools, and teacher enthusiasm for good relationships with students. In other words, it appears that a fixed career as a teacher is necessary in the formation of a teacherâs professional identity. However, teacher identity can be reconstructed as professional teaching experience is accumulated, as a result of school development policies, and as a result of teachersâ own forward-looking efforts to develop their careers. KEY WORD: Participation in building a schoolâs educational program, teachersâ professional identity, and career formation for teaching personnel at private schools.IKHTISAR: âFaktor-faktor Utama dalam Merekonstruksi Identitas Guru: Analisis Hasil Survei Kuesioner terhadap Lima Sekolah Menengah atau Atas Swasta di Wilayah Kota Tokyo Raya, Jepangâ. Penelitian ini adalah tentang pembentukan karier bagi tenaga pengajar di sekolah-sekolah swasta. Sebuah survei kuesioner guru penuh waktu di lima sekolah menengah atau sekolah atas dilakukan di Kota Tokyo Raya, Jepang. Hasil yang berbeda berdasarkan usia (perbedaan antara guru 40 tahun dan di atasnya, dan mereka yang di bawah 40 tahun) diperoleh sebagai hasil dari analisis ini. Dalam kasus guru di bawah 40 tahun, sekolah dimana mereka bekerja, tingkat kualitas siswanya, dan upaya yang dilakukan oleh sekolah tidak memiliki pengaruh yang signifikan terhadap identitas profesional guru. Identitas profesional guru yang berusia 40 tahun dan di atasnya, bagaimanapun, secara signifikan dipengaruhi oleh faktor-faktor seperti tingkat kualitas siswa, kebijakan manajemen sekolah, termasuk upaya-upaya positif untuk mengaktifkan sekolah, dan antusiasme guru untuk menjalin hubungan baik dengan siswa. Dengan kata lain, tampak bahwa karier yang pasti sebagai guru diperlukan dalam pembentukan identitas profesional guru. Namun, identitas guru dapat direkonstruksi sebagai pengalaman mengajar profesional yang terakumulasi, sebagai akibat dari kebijakan pengembangan sekolah dan akibat dari upaya guru sendiri untuk mengembangkan kariernya di masa depan.KATA KUNCI: Partisipasi dalam membangun program pendidikan sekolah, identitas profesional guru, dan pembentukan karier bagi tenaga pengajar di sekolah-sekolah swasta.About the Author: Yoshifumi Furuichi is a Student of Doctoral Program at the Graduate School of Regional Policy Design, Hosei University, Ichigayatamachi Shinjyuku-ku, Tokyo 162-0843, Japan. For academic interests, the author is able to be contacted via phone at: +81-3-5228-1640 or e-mail at: yreseacherf@yahoo.co.jpHow to cite this article? Furuichi, Yoshifumi. (2014). âChief Factors in the Reconstruction of Teacher Identity: Analysis of Results of a Questionnaire Survey Conducted at Five Private Middle or High Schools in the Greater Tokyo Area, Japanâ in ATIKAN: Jurnal Kajian Pendidikan, Vol.4(2) December, pp.113-130. Bandung, Indonesia: Minda Masagi Press, FKIP UNSUR Cianjur, and FPOK UPI Bandung, ISSN 2088-1290. Â  Â Chronicle of the article: Accepted (September 3, 2014); Revised (October 5, 2014); and Published (December 27, 2014).